2011
DOI: 10.1371/journal.pone.0027802
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal Domain and Glycosomal Localization of Leishmania Initial Acyltransferase LmDAT Are Important for Lipophosphoglycan Synthesis

Abstract: Ether glycerolipids of Leishmania major are important membrane components as well as building blocks of various virulence factors. In L. major, the first enzyme of the ether glycerolipid biosynthetic pathway, LmDAT, is an unusual, glycosomal dihydroxyacetonephosphate acyltransferase important for parasite's growth and survival during the stationary phase, synthesis of ether lipids, and virulence. The present work extends our knowledge of this important biosynthetic enzyme in parasite biology. Site-directed mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…To assign protein enrichment across the subcellular fractions, a spectral count methodology was employed because it gave a more robust agreement with the known subcellular localization of the above training set of 161 soluble proteins. Examination of the glycosomal markers (dihydroxyacetone phosphate acyltransferase, hexokinase, GMP reductase, and IMPDH components of the ether phospholipid biosynthesis, glycolysis, and purine salvage pathways ,, ) as well as the membrane proteins peroxin (PEX) 2, 11, 12, and 13, and the transporter GAT2 showed that these proteins were found primarily in fractions 27–31 (glycosomes) (Table and Table S2). Interestingly, other well-characterized glycosomal enzymes involved in purine salvage xanthine phosphoribosyltransferase (XPRT) and HGPRT , and the glycolytic enzyme triose phosphate isomerase were also detected in fractions 1–4 (with a density of ∼1.10 to 1.12 g/mL) of the glycosome fractionation (Table and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…To assign protein enrichment across the subcellular fractions, a spectral count methodology was employed because it gave a more robust agreement with the known subcellular localization of the above training set of 161 soluble proteins. Examination of the glycosomal markers (dihydroxyacetone phosphate acyltransferase, hexokinase, GMP reductase, and IMPDH components of the ether phospholipid biosynthesis, glycolysis, and purine salvage pathways ,, ) as well as the membrane proteins peroxin (PEX) 2, 11, 12, and 13, and the transporter GAT2 showed that these proteins were found primarily in fractions 27–31 (glycosomes) (Table and Table S2). Interestingly, other well-characterized glycosomal enzymes involved in purine salvage xanthine phosphoribosyltransferase (XPRT) and HGPRT , and the glycolytic enzyme triose phosphate isomerase were also detected in fractions 1–4 (with a density of ∼1.10 to 1.12 g/mL) of the glycosome fractionation (Table and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…DHAPAT enzymes from Leishmania ( Al-Ani et al, 2011 ) and Trypanosoma ( Zufferey et al, 2017 ) are much larger than their mammalian counterparts because they contain an N-terminal extension of unknown function. Interestingly, the ciliate Tetrahymena encodes the same bifunctional FARAT protein ( Dittrich-Domergue et al, 2014 ) as Dictyostelium , where the N-terminal extension encodes a functional fatty acid reductase domain ( Dittrich-Domergue et al, 2014 ) that may provide the fatty alcohol for the subsequent step in ether lipid synthesis ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glycolysis compartmentalization in the glycosomes prevents the accumulation of toxic intermediates generated during glucose degradation [35] . A recent study showed that glycosomal localization of Leishmania major dihydroxyacetonephosphate acyltransferase is important for lipophosphoglycan synthesis [36] .…”
Section: Discussionmentioning
confidence: 99%